2006
DOI: 10.1177/008124630603600209
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise and Psychological Well-Being

Abstract: This study was contextualised within a public health model of mental health promotion, with psychological well-being conceptualised as the positive component of mental health and physical exercise conceptualised as a subset of physical activities aimed at improving health and well-being. The research investigated the relationship between regular physical exercise over a period of two to six months and psychological well-being in 26 exercisers at health clubs in the Richards Bay area of South Africa. Psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 33 publications
2
43
1
6
Order By: Relevance
“…2001, Nguyen-Michel ve ark. 2006, Edwards 2006. Ayrıca araş-tırma sonuçları, bütünlük duygusu ile psikolojik sağlık arasında doğrudan ilişkinin varlığına işaret etmektedir.…”
Section: Bütünlük (Tutarlılık) öLçeği (Sense Of Coherence Scale)unclassified
“…2001, Nguyen-Michel ve ark. 2006, Edwards 2006. Ayrıca araş-tırma sonuçları, bütünlük duygusu ile psikolojik sağlık arasında doğrudan ilişkinin varlığına işaret etmektedir.…”
Section: Bütünlük (Tutarlılık) öLçeği (Sense Of Coherence Scale)unclassified
“…We have added the following categories: individual physical exercises and exercises in group. Some of the new studies [10] emphasize, that physically active students have better stress management level than those not active. It has been found that the most popular exercises were aerobics and fitness [10].…”
Section: Categories Of the Techniquesmentioning
confidence: 99%
“…Most of these studies highlight that those who engage in physical activity tend to have fewer stress symptoms compared to those who lead a more sedentary lifestyle. (13,14) Mandatory physical education classes are part of the school curriculum, and it's incorporated in the school time table itself. But when a student comes out of the school and joins a college or university, it is mostly left to his or her wish.…”
Section: Introductionmentioning
confidence: 99%